Enhancing the Institutional Capacity of Farmer Groups through Data Management and Administrative Counseling at the BPP of Bukit Kapur District, Dumai City - Fara Shaliza; Nurul Hasana; Sinta Fransiska (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Farmer group institutions play a strategic role in supporting agricultural development; however, many farmer groups still face limitations in data management and institutional administration. These limitations often hinder effective planning, accurate decision-making, transparency, and access to various agricultural development programs and partnerships. This Community Service Program (PKM) aims to enhance farmers’ understanding and practical skills in data management and institutional administration through structured extension activities conducted at the Agricultural Extension Center (BPP) of Bukit Kapur Subdistrict, Dumai City. The methods applied include lectures to introduce basic concepts, interactive discussions to encourage knowledge exchange, and hands-on practice in preparing, organizing, and managing farmer group administrative records. A participatory approach was employed to actively involve participants throughout the program. The results indicate a significant improvement in participants’ knowledge and skills related to farmer group administration, along with increased awareness of the importance of orderly and accountable administrative management. In addition, the program fostered a collective commitment to implementing sustainable and systematic record-keeping practices. Furthermore, the activities encouraged the emergence of local leadership and strengthened farmer group institutions as social capital, contributing to greater farmer independence, organizational resilience, and long-term welfare improvement.